INTERNALISASI NILAI-NILAI BUDAYA GORONTALO â€œRUKUNO LO TAALIYAâ€ DALAM PENETAPAN HARGA JUAL PADA PEDAGANG TRADISIONAL DI KOTA GORONTALO - Anwar, Fitria; Amaliah, Tri Handayani; Noholo, Sahmin (JURNAL AKUNTANSI DAN AUDITING, 2015)
The aim of this study was to describe how to determined traditional selling price based on Gorontaloâ€™s culture value, Rukuno Lo Taaliya. This study was a qualitative research by using Â ethnometodology approach. The results of this study indicated that in setting the selling price based on â€œRukuno Lo Taaliyaâ€ embodied some value such as honesty, mutual help, sincerity, trust and deep affection. These values reflected gratefulnees to God as part ofÂ  the worship and shadaqah. Selling price was notÂ  strictly formed by Â the things relating money but also Â reflected the common value which is believed by the cultural society.